Development Of Drilling Fluid System Using Carboxymethyl Cellulose (Cmc) For High Temperature-High Pressure (Hthp) Applications - Loong, Winson Sia Shen (2012)
This dissertation deals with a means of reducing the effects of thermal degradation that commonly occurs in drilling fluids. The objective of this dissertation is to determine the viability of the interaction between carboxymethyl cellulose (CMC) with bentonite to increase the resistance of water based drilling to high temperature degradation which normally occurs at 121⁰C. Drilling fluids are used in drilling operations for many purposes such as removing drill cuttings and cooling the drill bit. These days, petroleum supply are running low causing drilling operations to move further offshore which requires drilling fluids that are able to withstand high temperatures up to 177oC as well as high pressures up to 15ksi. Therefore, there is a need to develop drilling fluids for high temperature and high pressure (HTHP) applications. The degradation of drilling fluids results in changes of the drilling fluid properties such as viscosity and fluid loss control. Drilling fluids of various CMC-bentonite ratio are prepared and properties such as viscosity, gel strength, density as well as pH of the samples are studied. High temperatures of 200⁰C are then applied to the samples for a duration of 16 hours and changes in the properties of the drilling fluids of various CMC-bentonite content are observed. Results show that CMC-Bentonite interaction is a possible solution to thermal degradation of drilling fluids at HTHP conditions at 10% weight composition of CMC. However, further study needs to be conducted at CMC compositions below 10% to further verify this finding.